Save our cultural property with hearth - Ismail, Sumarni; Utaberta, Nangkula; Mohd Yunos, Mohd Yazid; Ismail, Nor Atiah; Mohd Arifin, Noor Fazamimah (American-Eurasian Network for Scientific Information (AENSI) Publications, 2015)
Cultural heritage is confronted with flood risks, especially in disaster –prone areas of river basin. In the context of Kelantan, Malaysia, one of the main issues stems from the limited official understanding of cultural heritage, which is still monument-centred and does not considered many important heritage components as worthy of protection. This paper is a presenting a research proposal on a flood preparedness strategy framework in Malaysia.